Nanocompositional Electron Microscopic Analysis and Role of Grain Boundary Phase of Isotropically Oriented Nd-Fe-B Magnets - Gregor A. Zickler; Josef Fidler (Advances in Materials Science and Engineering)
Nanoanalytical TEM characterization in combination with finite element micromagnetic modelling clarifies the impact of the grain misalignment and grain boundary nanocomposition on the coercive field and gives guidelines how to improve coercivity in Nd-Fe-B based magnets. The nanoprobe electron energy loss spectroscopy measurements obtained an asymmetric composition profile of the Fe-content across the grain boundary phase in isotropically oriented melt-spun magnets and showed an enrichment of iron up to 60 at% in the Nd-containing grain boundaries close to Nd2Fe14B grain surfaces parallel to the c-axis and a reduced iron content up to 35% close to grain surfaces perpendicular to the c-axis. The numerical micromagnetic simulations on isotropically oriented magnets using realistic model structures from the TEM results reveal a complex magnetization reversal starting at the grain boundary phase and show that the coercive field increases compared to directly coupled grains with no grain boundary phase independently of the grain boundary thickness. This behaviour is contrary to the one in aligned anisotropic magnets, where the coercive field decreases compared to directly coupled grains with an increasing grain boundary thickness, if Js value is > 0.2 T, and the magnetization reversal and expansion of reversed magnetic domains primarily start as Bloch domain wall at grain boundaries at the prismatic planes parallel to the c-axis and secondly as Néel domain wall at the basal planes perpendicular to the c-axis. In summary our study shows an increase of coercive field in isotropically oriented Nd-Fe-B magnets for GB layer thickness > 5 nm and an average Js value of the GB layer < 0.8 T compared to the magnet with perfectly aligned grains.